Implementasi Wireless Sensor Network pada Pemantauan Kondisi Struktur Bangunan Menggunakan Sensor Accelerometer MMA7361 - Era Imanningtyas; Sabriansyah Rizqika Akbar; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The Building is one of the most important facilities and infrastructure in human life. Therefore, when a building is damaged whether it is caused by a natural disaster that can not be predicted or the age of the building itself will have a profound effect on human life. To overcome this problem is by applying wireless sensor network to monitoring the vibration response of building a structure using MMA7361 accelerometer sensor, Arduino Uno microcontroller, nRF24L01 transceiver module, Personal Computer (PC) and Delphi 2010 monitoring application. So it can be easier, compact and low power, but can collect all the information in the form of vibration acceleration data obtained from each client node sent to the node server periodically and displayed graphically as well as the value of vibration acceleration data on the Personal Computer (PC) using Delphi 2010 monitoring applications, without the user must monitor the intended object directly. As a result, each node client is able to transmit vibration acceleration data obtained from several types of wooden, plywood, and concrete structure structures to the server nodes. Thus, the data obtained from the type of wooden structure has an average of vibration acceleration sampling data of 6,1 m/s2. The plywood building structure has an average value of vibration acceleration sampling data of 116 m/s2. Meanwhile, the concrete structure has an average of vibration acceleration sampling data of 0 m/s2. All tested in one hit test.